Implementasi Media Video Kasus dalam Menumbuhkan Motivasi Membaca dan Sikap Toleransi di SD Surakarta: Implementation of Video Case Media in Cultivating Reading Motivation and Tolerance in Surakarta Elementary Schools - Naptaviona Riyanti Sofanty; Arief Cahyo Utomo (ITScience (Information Technology and Science), 2026)
This study aims to analyze the implementation of case video media in Pancasila and Citizenship Education (PPKn) learning to increase reading motivation and foster tolerance in elementary school students. The study used a descriptive qualitative approach and was conducted in the fourth grade of Muhammadiyah 02 Elementary School, Kauman, Surakarta, with one teacher and 28 students as subjects. Data collection techniques included observation, interviews, and documentation, which were analyzed through data reduction, data presentation, and conclusion drawing. Their validity was tested using triangulation. The results showed that the use of case video media increased students' reading motivation, as demonstrated by five indicators: perseverance, independence, positive interest, active involvement, and environmental support.Furthermore, this media was also effective in fostering tolerance in students, reflected in the ability to appreciate differences, respect others' beliefs, be open, love peace, and demonstrate social awareness. Case video media provided a contextual and engaging learning experience, making it easier for students to understand the material and internalize social values. Learning became more interactive and encouraged active student participation in both reading and social interactions. Thus, the implementation of case video media not only contributes to improved reading literacy but also plays a crucial role in the holistic development of students' tolerant character. This study recommends the use of innovative, context-based learning media to support literacy and character development in elementary schools.